Review and discussion of modern concepts and its relation to the research in Poland - Dobiński, Wojciech (Quaestiones Geographicae, 2024)
This paper describes the foundations of the periglacial concept beginning from the introduction of this term by Łoziński in 1909 and 1912. Its etymology along with the meaning and definitions that change over time are analysed in the present paper. Originally derived from geology, periglacial now functions as a geomorphological term. It has been compared with other terms used in the characterisation of cold geographical environments; the role of freezing and ice has been especially emphasised for periglaciology, and the most important types of ice have been highlighted. The present paper aims to show that with the increasing specialisation of research and the evolution of the meaning of the term periglacial, it is still seen as playing an important integrating role. The relation of the periglacial environment and ice to the glacial environment is also presented, showing the places of mutual overlapping of both environments. Old and newly introduced terms related to this concept such as periglacial facies, periglacial landscape, paraglacial, and cryo-conditioning are critically assessed. Finally, a short description of the permafrost in Poland, occurring in two remote and specific places, is presented: the active mountain permafrost covering the alpine belt of the Tatra Mountains about 1900 m a.s.l. and the relict permafrost in the Suwałki area, located in the northern lowland of Poland at a depth of 357 m and below.